A single switch high step‐up DC‐DC converter with three winding coupled inductor. (18th July 2018) - Mahmoudi, Mohsen; Ajami, Ali; Babaei, Ebrahim
Summary: A new high gain DC‐DC converter based on single switch and three‐winding coupled inductor is presented in this paper. Existence of a three‐winding coupled inductor in suggested topology has led to lift voltage gain by low number of windings' turn ratio. As a result, the main advantage of the proposed converter is to produce a high voltage gain without great values of duty cycle. The passive clamped technology is used in the proposed converter. It causes better performance for proposed converter by recycling the leakage inductance energy as well as restricting voltage stress by reducing great voltage spikes. In this paper, performance analysis and mathematical equations of the proposed converter are explained. In addition, variations of voltage gain as a result of leakage inductance and voltage and current stresses of power devices are studied, too. Moreover, performance of the suggested converter and the previously presented high gain ones are compared with together. Lately, a 200‐W prototype is constructed, and the experimental results approve the effectiveness of the proposed converter.